Influence Of Transverse Elements On The Pullout Capacity Of Metal Strip Reinforcement In Sandy Soil - Javad, Esfandiari (2014)
Interface friction angle between different materials is a very important parameter in the designs of mechanically stabilized earth (MSE) as it corresponds directly to pull out capacity of a reinforcement strip. In this research, anchorage elements have been added to normal reinforcement strip in order to increase interface friction angle and thus the pull out capacity. Sand was used as fill material. In the tests, one plain strip with smooth surface, two strips with simple ribs, and eighteen strips with transverse members of various depths and counts were subjected to pull out forces with normal stresses ranging from 50 kPa to 100 kPa applied. Also, π-Buchingham theorem and regression analysis using statistical software - SPSS v.14 - were used to obtain general equations relating pull out capacity to strip parameters and compare predicted strength values to actual outcomes of the tests. The results of the study indicate that the new method involving transverse members could generally offer saving of strip material or provide particular design criteria for MSE of limited construction space, since the increased capacity of each reinforcement strip would reduce the total length or amount of strips required in a project.